Electrical switching between exciton dissociation to exciton funneling in MoSe2/WS2 heterostructure - Yuze Meng (Nature Portfolio, 2020)
The ultrafast carrier dynamics across the van der Waals interface of transition metal dichalcogenide heterostructures govern the formation and funnelling of excitons. Here, the authors demonstrate a reversible switch from exciton dissociation to exciton funnelling in a MoSe2/WS2 heterostructure, which manifests itself as a photoluminescence quenching-to-enhancement transition.